Foot Disorders in Nursing Standing Environments: A Scoping Review Protocol - Bernardes Rafael A.; Parreira Pedro; Sousa Liliana B.; Stolt Minna; Apóstolo João; Cruz Arménio (MDPI, 2022)
Musculoskeletal disorders can be significantly disabling, particularly those related to work, when the underlying mechanisms and clinical variables are not well known and understood. Nurses usually remain in standing positions or walk for long periods, thus increasing the risk for the development of musculoskeletal disorders, particularly on the foot, such as plantar fasciitis or edema. This type of disorders is a major cause of sickness, absence from work, and also dropout ratios among nursing students, which contributes to the shortage of nursing professionals. This review will address foot disorders that arise from prolonged standing in nursing professionals and describe the main clinical parameters characterizing them, with exclusions for other health professions or disorders with other identified causes. English, French, Portuguese, and Spanish published studies from 1970 to the current year will be considered. The review will follow the JBI methodology, mainly though the PCC mnemonic, and the reporting guidelines for Scoping Reviews. The search will include main databases and relevant scientific repositories. Two independent reviewers will analyze the titles, abstracts, and full texts. A tool developed by the research team will aid in the data collection.